Noisy little truck - Baxter, Nicola; Straaten, Harmen van (Ladybird Loughborough, 1997)
All is quiet in the town square - until Little Truck arrives with a rattle and a rumble and a beep, beepity, BEEP! How can he make his daily deliveries without causing mayhem?